Role of lecturer emotional management in driving student satisfaction in Sri Lankan private higher education: insights from ABC Institute - Wijesinghe T; Kariyawasam S. S; Herath, D. (Sri Lanka Institute of Information Technology (SLIIT): Malabe, 2025)
Emotional intelligence encompasses the capacity to comprehend, regulate, and articulate emotions proficiently, along with the ability to connect empathetically with others. Research on the specific emotional intelligence traits of academics that affect student satisfaction in Sri Lanka's private tertiary education sector remains scarce, despite its significance. This study examines the influence of academics’ emotional intelligence (EI) characteristics on the satisfaction levels of undergraduate students in Sri Lankan private tertiary education institutions, specifically focusing on ABC Institute. As emotional intelligence becomes increasingly recognized as a crucial factor in effective teaching and student engagement, this study analyses how various EI dimensions such as self-awareness, empathy, concern for well-being, emotional regulation, and interpersonal skills affect overall student satisfaction. Utilizing a multi method approach in the first phase of the study, authors interviewed 21 students and did a systematic journal review to identify underpinning emotional intelligence themes affecting student satisfaction and in the second stage data was gathered through a structured questionnaire from 278 students with representation from different study streams. The results of both phases indicated that there is a significant relationship exist between elevated levels of academic emotional intelligence and enhanced student satisfaction, particularly in aspects like student-teacher academic relationship, student engagement, teacher self-efficacy and lecturer’s enthusiasm on student well-being. The study underscores the importance of incorporating emotional intelligence training into the professional development of academic staff to improve educational quality and student experiences. It also offers recommendations for policy and practice aimed at fostering sustainable advancements in Sri Lanka's higher education sector.
Keywords: Emotional Intelligence; Higher Education; Student Satisfaction